Assessing oral presentation skills in Electrical Engineering: Developing a valid and reliable rubric - Galván-Sánchez, Inmaculada; Verano-Tacoronte, Domingo; González-Betancor, Sara M; Fernández-Monroy, Margarita; Bolívar-Cruz, Alicia (International journal of electrical engineering & education, 2017)
Oral presentation is one of the most important transversal competences for the professional career of Electrical Engineers. To develop and assess this competence, scoring rubrics are useful academic tools. The main purpose of this study is to contribute to the understanding of the learning and assessment of oral presentation skills of future Electrical Engineers by using a scoring rubric as a teaching resource. A pilot experiment was carried out in the 2011/2012 academic year in a course in the ninth semester of Electrical Engineering studies with 64 students. In order to acquire the oral competence, students had to present a marketing plan for an industrial electrical project in front of an audience. Feedback was collected in meetings held with teachers and students after the presentations. As a result, the need to review the rubric was detected, in order to make its use easier. The rubric’s design was improved. In the 2012/2013 academic year, 86 students participated in a new experiment using the improved rubric in the same subject. Intra-rater consistency was shown by the scale’s reliability, measured with Cronbach’s alpha. Regarding inter-rater consistency, two procedures were used: holistic and analytic. The holistic procedure revealed a positive and relatively high correlation between the global scores given by each of the two raters. The analytic procedure showed an acceptable level of inter-rater consensus. Through a questionnaire, quantitative data were collected reflecting students’ satisfaction with the use of the improved scoring rubric. The results reveal the rubric promotes students’ learning by providing them with a clear orientation to improve their performance on current academic assignments and in future professional situations. So, the analyses show that the proposed rubric is valid, reliable and, suitable to teach and assess oral presentations in a simulated professional scenario for Electrical Engineers.